GW24-e1885 Angiotensin II type 1 receptor mediates cardiomyocyte autophagy induced by angiotensin II through p38 MAPK signal pathway. (1st October 2013) - Li, Lin; Xu, Jianfeng; Ye, Yong; Ge, Junbo; Zou, Yunzeng; Liu, Xuebo
Abstract : Objectives: Autophagy plays an important role in the development of angiotensin II (Ang II)-induced cardiac remodelling. However, the mechanism has not been completely understood. This study is designated to investigate the mechanism involved in the Ang II-induced cardiomyocyte autophagy. Methods: We investigated the role of angiotensin II type 1 (AT1) receptor and mitogen-activated protein kinase (MAPK) in Ang II-induced autophagic response in cultured cardiomyocytes. LC3b, a marker of autophagy, was detected by western blot analysis. In addition, mice were infused of Ang II for 4 weeks to test the effect of autophagy. Results: After Ang II stimulation (48 hours), neonatal cardiomyocytes expressed hypertrophic responses and remarkable up-regulation of LC3b. While olmesartan, an AT1 receptor antagonist, not only attenuated cardiac hypertrophy but also abrogated up-regulation of LC3b induced by Ang II. And treatment with PD123319, the AT2 receptor antagonist, did not reverse Ang II-induced autophagy. We also investigated the change of activity of MAPK pathway in the autophagy induced by Ang II. We found that the phosphorylation of ERK, JNK and p38 were significantly increased after stimulation compared with control group. The increase of LC3b was significantly blocked by SB 203580, a p38 MAPK inhibitor. However, treatment with PD98059, an ERK inhibitor, or SP600125, a JNK inhibitor, did not abrogate the Ang II-induced autophagy. AT1 mediated autophagic and hypertrophic responses were also assessed in vivo . The expression of LC3b in left ventricular cardiomyocyte increased significantly in AngII-treated mice compared with that in sham mice. And olmesartan significantly inhibited the up-regulation of LC3b induced by Ang II. Moreover, olmesartan also ameliorated cardiac remodelling and dysfunction induced by Ang II after 4 weeks. Conclusions: The results indicate that autophagy in cardiomyocytes induced by Ang II is AT1 receptor-dependant, and is through p38 MAPK signal pathway.